Azide-functionalized lanthanide-based metal-organic frameworks showing selective CO2 gas adsorption and postsynthetic cavity expansion - Ganguly, Sumi; Pachfule, Pradip; Bala, Sukhen; Goswami, Arijit; Bhattacharya, Sudeshna; Mondal, Raju (Inorganic Chemistry, 2013)
We report herein selective CO2 gas adsorption by two azide-functionalized lanthanide-based metal-organic frameworks (MOFs). This work also demonstrates that azide-functionalized MOFs can be used for postsynthetic cavity expansion, further corroborated by enhanced gas-sorption data.

Comprehensive study on mutual interplay of multiple V-shaped ligands on the helical nature of a series of coordination polymers and their properties - Goswami, Arijit; Bala, Sukhen; Pachfule, Pradip; Mondal, Raju (Crystal Growth & Design, 2013)
{V-shaped ligands are commonly used for helical coordination polymer synthesis. However, employment of multiple V-shaped ligands does not always lead to a helical network. The mutual interplay of two V-shaped ligands, which is neither easily predictable nor well documented, plays a major role directing the self-assembly of the resultant network. We report here the construction of a series of novel coordination polymers {[Ni(OBA)(H2MDP)(H2O)]center dot(DMF)(3)}(n) (1),{[Ni(FBA)(H2MDP)]center dot(H2O)(3)center dot(DMF)\

Construction of polynuclear lanthanide (Ln = Dy-III, Tb-III, and Nd-III) cage complexes using pyridine-pyrazole-based ligands: versatile molecular topologies and smm behavior - Bala, Sukhen; Sen Bishwas, Mousumi; Pramanik, Bhaskar; Khanra, Sumit; Fromrn, Katharina M.; Poddar, Pankaj; Mondal, Raju (Inorganic Chemistry, 2015)
Employment of two different pyridyl pyrazolyl-based ligands afforded three octanudear lanthanide(III) (Ln = Dy, Tb) cage compounds and one hexanudear neodymium(III) coordination cage, exhibiting versatile molecular architectures including a butterfly core. Relatively less common semirigid pyridyl pyrazolyl-based asymmetric ligand systems show an interesting trend of forming polynuclear lanthanide cage complexes with different coordination environments around the metal centers. It is noteworthy here that construction of lanthanide complex itself is a challenging task in a ligand system as soft N-donor rich as pyridyl pyrazol. We report herein some lanthanide complexes using ligand containing only one or two O-donors compare to five N-coordinating sites. The resultant multinuclear lanthanide complexes show interesting magnetic and spectroscopic features originating from different spatial arrangements of the metal ions. Alternating current (ac) susceptibility measurements of the two dysprosium complexes display frequency- and temperature-dependent out-of-phase signals in zero and 0.5 T direct current field, a typical characteristic feature of single-molecule magnet (SMM) behavior, indicating different energy reversal barriers due to different molecular topologies. Another aspect of this work is the occurrence of the not-so-common SMM behavior of the terbium complex, further confirmed by ac susceptibility measurement.

Ln(8) (Ln = Gd, Ho, Er, Yb) Butterfly core-exhibiting magnetocaloric effect and field-induced SMM behavior for Er analouge - Bala, Sukhen; Adhikary, Amit; Bhattacharya, Sudeshna; Sen Bishwas, Mousumi; Poddar, Pankaj; Mondal, Raju (ChemistrySelect, 2017)
In this article, we report four pyridyl-pyrazolyl based poly-nuclear cluster complexes with Ln(8) {Ln = [Gd-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(2)(MeOH)(1), [Ho-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](2), [Er-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(H2O)(3), [Yb-8(III)(mu(3)-OH)(4)(L-1)(4)(DEA)(4)Cl-4](DMF)(MeOH)(4) [DEA = Diethanolamine] cores. The impetus for this study was to explore the magnetic behaviour of lanthanide ions which are often ignored or overlooked. X-ray crystal analysis show that these complexes are isostructural and exhibit an interesting butterfly like topology. The semi-rigidity and asymmetric nature of the ligand led to different coordination environment around the metal centres. The lanthanide ions adopt two types of geometry, a bicapped trigonal prism and a distorted square antiprismatic geometry around the metal center. Such dissimilar coordination environments around the lanthanide centre can have profound effects on their magnetic behaviour. Indeed, the magnetic measurements revealed significant magnetocaloric effect for octanuclear gadolinium complex 1 with magnetic entropy change (-Delta S-m ) of 31.4 J kg(-1) K-1 for Delta H = 9 T at T = 3 K whereas Er analogue complex 3 displayed SMM behavior.